2019
DOI: 10.1155/2019/9521529
|View full text |Cite
|
Sign up to set email alerts
|

Direct Benzyl Alcohol and Benzaldehyde Synthesis from Toluene over Keggin-Type Polyoxometalates Catalysts: Kinetic and Mechanistic Studies

Abstract: e catalytic activity of various Keggin polyoxometalate catalysts has been investigated in the gas-phase partial oxidation of toluene to produce benzyl alcohol and benzaldehyde. e catalyst systems HPMo 12 O 40 , HPMo 11 VO 40 , FePMo 12 O 40 , and PMo 11 FeO 39 were prepared and characterized by FT-IR, UV-visible, SEM, XRD, TGA, and cyclic voltammetry. e acid/base properties were evaluated using the decomposition of isopropanol. Catalytic studies were carried under atmospheric pressure and over the temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…The oxidation of primary alcohols by POM catalysts has already been investigated and confirmed in the literature. [58][59][60][61] However, previous results on the free furan system in the form of furfuryl alcohol have shown that the intermediates 2(5H)-furanone and 5-hydroxyfuran-(25H)-furanone and the final product of this pathway (using free furan systems), maleic acid, were almost not formed. 23 Instead of maleic acid, products such as succinic acid and levulinic acid were detected, indicating a different mechanism.…”
Section: Reaction Chemistry and Engineeringmentioning
confidence: 96%
“…The oxidation of primary alcohols by POM catalysts has already been investigated and confirmed in the literature. [58][59][60][61] However, previous results on the free furan system in the form of furfuryl alcohol have shown that the intermediates 2(5H)-furanone and 5-hydroxyfuran-(25H)-furanone and the final product of this pathway (using free furan systems), maleic acid, were almost not formed. 23 Instead of maleic acid, products such as succinic acid and levulinic acid were detected, indicating a different mechanism.…”
Section: Reaction Chemistry and Engineeringmentioning
confidence: 96%
“…It is also one of the most important chemicals in the aromatic aldehyde family. [1] For industrial purposes, benzaldehyde derivatives are used as a building block for a large number of products, including the production of perfume, beverage, pharmaceuticals, plastic additives, chromium trioxide, dichromate and so on. [2] The fine chemical sector has grown dramatically over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic aldehydes like benzaldehyde (BzH), the second most produced and valuable natural fruit flavour, are flavouring molecules with a distinctive bitter almond taste and odour. It is also one of the most important chemicals in the aromatic aldehyde family [1] . For industrial purposes, benzaldehyde derivatives are used as a building block for a large number of products, including the production of perfume, beverage, pharmaceuticals, plastic additives, chromium trioxide, dichromate and so on [2] .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, noble metal catalysts were also used in a benzaldehyde preparation process [14,15]. Although the use of noble metals significantly increases the cost of the catalytic reaction, few reports to date have investigated the combination of oxygen and transition metal oxide catalysts in the catalytic oxidation of cinnamaldehyde.…”
Section: Introductionmentioning
confidence: 99%